Life situations and the care burden for stroke patients and their informal caregivers in a prospective cohort study. (2nd October 2015) - Olai, Lena; Borgquist, Lars; Svärdsudd, Kurt
Abstract: Background. The purpose of this study was to analyse whether the parallel life situation between stroke patients and their informal caregivers (dyads) shown in cross-sectional studies prevails also in a longitudinal perspective. Methods. A total of 377 Swedish stroke patients, aged ≥65 years, and their 268 informal caregivers were followed from hospital admission and one year on. Analyses were based on patient interviews, functional ability (MMSE) score, Nottingham Health Profile (NHP) score, Hospital Anxiety and Depression (HAD) score, self-rated health score, and the Gothenburg Quality of Life (GQL) activity score. Similar information was obtained by postal questionnaires from informal caregivers, also including information on the nature and amount of assistance provided and on Caregiver Burden (CB) score. Results. Before index admission informal caregivers provided care on average 5 h per week and after discharge 11 h per week ( P < 0.0001). Support volume was associated with patient sex (more for men), low patient's functional ability, low received municipal social service support, closeness of patient–caregiver relation, and short distance to patient's home. Significant positive associations within the dyads were found for HAD anxiety score ( P < 0.0001), total NHP score ( P < 0.0001), and GQL activity score ( P < 0.0001) after adjustment for patient's age, sex, functional ability, and patient–caregiver relationship. CB score increased with amount of informal caregiver support, patient's age, and with low functional ability and low amount of municipal social service support. All these associations were constant across time. Conclusions. There was an association within the dyads regarding anxiety score, NHP score, and activity score. CB score was generally high.